The Lateral Fibular Stress Test: High Variability of Force Applied by Orthopaedic Surgeons in a Biomechanical Model. Issue 2 (June 2022) - Ingall, Eitan M.; Kaiser, Philip; Ashkani-Esfahani, Soheil; Zhao, John; Kwon, John Y.
Background: The lateral fibular stress test (LFST), also known as the hook or Cotton test, is commonly performed to assess syndesmotic instability intraoperatively. Several studies have used 100 N as the force applied when performing the LFST to detect syndesmotic instability, though no evidence-based requisite force has been described for the test. We hypothesize that surgeons do not apply force uniformly or consistently when performing the LFST and that substantial variation exists. Fundamentally, this could lead to inconsistent diagnosis of syndesmotic instability as surgeons may not be applying the force in a consistent manner. Methods: A biomechanical ankle model consisting of an industrial force gauge attached through a SawBones model was fashioned. Orthopaedic attending surgeons and trainees were asked to perform a series of LFSTs and to simulate the force they typically apply intraoperatively. Basic demographic data were collected on each participant. Results: Thirty-three surgeons participated in the study, including 18 trainees. The median (IQR) force applied during the LFST was 96.42 (71.42-126.33), 87.49 (69.19-117.40), 99.99 (79.91-137.49), for the pooled group, attendings, and trainees respectively. More than half (54.5%) of all trials were less than 100 N (57.8% of surgeons, 51.8% trainees). Intraobserver correlation was excellent within the overall cohort (0.92, P < .001), trainees (0.90, P < .001), and attendings (0.94, P < .001), respectively. Interobserver reliability was fair among the overall cohort (κ =0.28, P = .49), and poor between the attendings (κ = 0.11, P = .69) and the trainees (κ = 0.05, P = .82), respectively. Conclusion: Our study demonstrates that the amount of force applied by typical surgeons when performing the LFST test is highly variable. Variable force application when performing the LFST may lead to inconsistent detection of syndesmotic instability, which may portend a poorer outcome. Clinical Relevance: In this study, we demonstrate the wide variability in the amount of force used during a lateral fibular stress test. High variability of force application when performing the LFST may lead to inconsistent diagnosis of syndesmotic instability, which may portend a poorer outcome. Our findings suggest the need for further investigation into the technical aspects of syndesmotic testing that will permit more reproducible and valid interrogation of the syndesmosis.